The Impact of Information Asymmetry on the Relationship Between Board Characteristics and Capital Structure - Abdel-Wanis, Eman; Rashed, Ahmed (Journal of Applied Business and Economics, 2023)
This paper explores the role of information asymmetry in the association between board characteristics and capital structure using OLS & GMM for 96 firms listed on the Egyptian stock exchange with 672 firmobservation through the period 2014–2020 via the Thomson Reuters database. Results show that a large board size enhances strict control and forces increased debts to maximize firm value and higher board independence leads to the tendency to use less financial leverage to avoid raising risks. CEO duality leads to the use of small amounts of debt to avoid pressures and risks. Results show that Firms with high information asymmetry prefer high leverage. Finally, results clarified that board characteristics hurt capital structure in the case of countries that suffer from information asymmetry like Egypt.